2014
DOI: 10.3892/etm.2014.2059
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vascular endothelial growth factor by small interfering RNA upregulates differentiation, maturation and function of dendritic cells

Abstract: This study aimed to investigate the effects of vascular endothelial growth factor (VEGF) secreted by MCF-7 breast cancer cells on the differentiation, maturation and function of dendritic cells (DCs). Small interfering RNAs (siRNAs) directed against the VEGF gene were designed and transfected into MCF-7 breast cancer cells at an optimal concentration (100 nmol/l) using cationic liposome transfection reagent, whereas the control group was transfected with only transfection reagent. Western blot analysis and ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Consistently, elevated DCs and reduced immature progenitor cells in peripheral blood have been detected in cancer patients after bevacizumab administration 80 . In vitro studies also suggest that supernatant from breast cancer cell lines with VEGF expression ablated by shRNA induces PBMC‐derived DCs to up‐regulate CD80, CD86, and HLA‐DR expression and enhances DC‐mediated T‐cell cytotoxicity 81 …”
Section: Effects Of Vegf On Myeloid Cellsmentioning
confidence: 67%
“…Consistently, elevated DCs and reduced immature progenitor cells in peripheral blood have been detected in cancer patients after bevacizumab administration 80 . In vitro studies also suggest that supernatant from breast cancer cell lines with VEGF expression ablated by shRNA induces PBMC‐derived DCs to up‐regulate CD80, CD86, and HLA‐DR expression and enhances DC‐mediated T‐cell cytotoxicity 81 …”
Section: Effects Of Vegf On Myeloid Cellsmentioning
confidence: 67%
“…The results of the present study indicated that Endostar treatment was able to increase IFN-γ and CD86 levels and decrease the level of IL-17 in HCC mice. VEGF may serve an important role in tumor development, progression and immunosuppression associated with CD86 ( 58 ). Therefore, it was hypothesized that vascular normalization of Endostar may be associated with the suppression on Th17 response and regulation on Th1/Th2 imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Перспективным направлением является терапия с использованием препаратов -«ловушек» VEGF (афлиберцепт), направленная на ингибирование сигнального пути VEGF и повышение количества зрелых ДК у пациентов с рефрактерными солидными опухолями [29]. В свою очередь, исследования in vitro продемонстрировали, что ингибирование экспрессии VEGF с помощью коротких интерферирующих РНК в клетках рака молочной железы эффективно восстанавливает процесс дифференцировки и созревания ДК, что увеличивает способность ДК индуцировать опухолеспецифический цитотоксический Т-клеточный ответ [30].…”
Section: обзоры литературыunclassified